An Analysis of The Impact of Shadow Economy in Small Construction Companies - Hans PRESULLI (Communications of International Proceedings, 2023)
Studies that peddle the future prospects with distorted media reports and only show the economic level with statistical key figures at a high level, where, however, the small building trade is underrepresented among the average values, their individuality is underrepresented. The motivation for this study/analysis) arose from the literature study in the course of the dissertation work, but also from my work in the construction field as an expert, up to the present day. During this it became apparent that highly qualified research deals with various aspects of small-scale construction companies, but not dynamic connections between these services in the surveys, interviews and papers. Large construction companies as well as organizations and state-run studies usually focus on the macroeconomic level, which serves to analyses trends, but rarely on microeconomic processes and connections, since the prevailing opinion is reflected or represented in key business figures. This simple observation eventually leads to a desensitization as the socio-cultural versus economic similarities spiral out of control. The study was carried out to manage the joint cooperation, which I miss in the research gap.  From a methodological point of view, interviews were held with key persons (company owners), as well as 10 questionnaires with 10 questions about the difficulties of the informal economy in small-scale construction. During this, discussions were held about the cooperation between managers and their employees. The literature referred to the studies of Dr. Friedrich Steiner, which contexts of the shadow economy are described, which the triangulation represents in an overall metric. The analysis of the influence of the shadow economy on the overall performance was supplemented, if necessary, by the author's empirical values to finally be able to present the research results categorically and to be able to finally discuss them.
Keywords: Shadow economy; Undeclared work; Sales decline